KETERWAKILAN POLITIK PEREMPUAN DI PARLEMEN PERIODE 2019-2024: PERAN PARTAI POLITIK - Nurdin Nurdin (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
Political parties have an important role in efforts to increase women's political representation in parliament. The most significant function of political parties as gatekeepers is to carry out the recruitment, selection and candidacy of candidates for members of parliament in the general election contestation. This study aims to explain both internal and external factors that influence the role of political parties in increasing women's political representation in parliament in the 2019 election. The research method used is literature study by referring to previous research and secondary data sourced from books, journals, online news, and laws and regulations. The findings of this study reinforce previous research that political parties have a major role in efforts to increase women's political representation in parliament. The role of the party refers to the process of recruitment, selection and candidacy of women, the involvement of women in the organizational structure of the party, and the ideology of political parties. The role and policies of political parties in increasing women's representation are also strongly influenced by gender quota policies, electoral systems and party systems, and women's movement activists.